Is Vascularized Composite Allograft Transplantation Experimental or an Accepted Surgical Procedure: Results from a National Survey - Colakoglu, Salih; Tebockhorst, Seth; Mathes, David Woodbridge (Journal of Reconstructive Microsurgery, 2020)
Background More than 85 patients have received over 100 hand/arm transplants and more than 35 patients have received full or partial face transplants at institutions around the world. Given over two decades of experience in the field and in the light of successful outcomes with up to 17 years follow up time, should we still consider vascularized composite allograft (VCA) as a research/clinical investigation? We present the results of a nationwide electronic survey whose intent was to gather institutional bias with regard to this question.Methods An 11 question survey that was developed by VCA advisory committee of American Society of Transplantation was sent to all identified Internal Review Board chairs or directors in the United States.Results We received a total of 54 responses (25.3%) to the survey. The majority (78%) of responses came from either the chairperson, director, or someone who is administratively responsible for an IRB.Conclusion Though certainly not an exhaustive investigation into each institution's preference, we present a representative sampling. The results of which favor VCA as an accepted clinical procedure given the appropriate setting. Further research is needed to fully ascertain practices at each individual institution.
Keywords: vascularized composite allograft; hand transplantation; face transplantation